Cytoplasmic protrusions from digestive cells of bees - Da Cruz-Landim, Carminda [UNESP]; Serrão, José Eduardo [UNESP]; Silva-de-Moraes, Regina Lúcia Morelli [UNESP] (My University, 1996)
Midgut cells from the honey bee, Apis mellifera, and the stingless bees Scaptotrigona postica and Melipona quadrifasciata anthidioides were examined ultrastructurally and histochemically. Several types of protrusions were evident in the apical surface of the midgut cells. Large apical protrusions formed by the whole apical surface of the cell, whose content had a homogeneous cytoplasmic matrix devoid of organelles and with a different electron density from the subjacent cytoplasm. These protrusions can be cast out to the midgut lumen. A second type of large apical protrusion was produced between the cell microvilli, presenting many ribosomes and polyribosomes. In addition to these large protrusions two other kinds of small ones were observed. One type crowned the cell apex forming small spheres with irregular contours near the cells, and increasing in size further away. The other type was characterized by the microvilli swelling with an electron-lucent content. The Gomori acid phosphatase reaction was positive at the cell apex, in the pinched off protrusions and in the microvilli. These results are discussed in relation to the possible role of cell protrusions in secretory mechanisms.
Keywords: Apis mellifera; Digestive tract; Midgut; Stingless bee; Ultrastructure